2023
DOI: 10.24215/23142561e245
|View full text |Cite
|
Sign up to set email alerts
|

Autoeficacia en profesores de Educación Física chilenos de la región del Ñuble: formación y desempeño profesional

Abstract: Este artículo analiza el constructo de autoeficacia, configurado como el conjunto de creencias sobre la capacidad para ejecutar planes de acción, en la práctica docente, en sujetos participantes de una investigación psicométrica realizada con educadores chilenos de la región del Ñuble y su relación con aspectos de formación y educación desempeño profesional, considerando variables sociodemográficas. Es un estudio transversal con alcance descriptivo y comparativo. Participaron 193 docentes de Educación Física d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…It is worth noting that both Covarrubias-Apablaza and Mendoza-Lira (2015) and Pérez Norambuena et al (2023) have reported that there are no significant differences between Chilean teachers of different genders in their perception of self-efficacy, which is endorsed by several international studies ( Sirmaci and Taş, 2016 ; Tárraga-Mínguez et al, 2022 ). In their studies, Covarrubias-Apablaza and Mendoza-Lira (2015) mention that men and women teachers feel able to engage, teach, manage, and care for their students.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…It is worth noting that both Covarrubias-Apablaza and Mendoza-Lira (2015) and Pérez Norambuena et al (2023) have reported that there are no significant differences between Chilean teachers of different genders in their perception of self-efficacy, which is endorsed by several international studies ( Sirmaci and Taş, 2016 ; Tárraga-Mínguez et al, 2022 ). In their studies, Covarrubias-Apablaza and Mendoza-Lira (2015) mention that men and women teachers feel able to engage, teach, manage, and care for their students.…”
Section: Introductionmentioning
confidence: 79%
“…These results align with the Peruvian study ( Dominguez-Lara et al, 2019 ) that provided evidence of measurement invariance between men and women. In addition, two previous Chilean studies that found no significant differences in teacher self-efficacy factors according to sex can be taken into account ( Covarrubias-Apablaza and Mendoza-Lira, 2015 ; Pérez Norambuena et al, 2023 ). Similar findings were reported in other countries ( Sirmaci and Taş, 2016 ; Tárraga-Mínguez et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations